Graphene-based CO2 sensing and its cross-sensitivity with humidity. Issue 36 (21st April 2017) - Smith, Anderson D.; Elgammal, Karim; Fan, Xuge; Lemme, Max C.; Delin, Anna; Råsander, Mikael; Bergqvist, Lars; Schröder, Stephan; Fischer, Andreas C.; Niklaus, Frank; Östling, Mikael
Abstract : We present graphene-based CO2 sensing and analyze its cross-sensitivity with humidity. Abstract : We present graphene-based CO2 sensing and analyze its cross-sensitivity with humidity. In order to assess the selectivity of graphene-based gas sensing to various gases, measurements are performed in argon (Ar), nitrogen (N2 ), oxygen (O2 ), carbon dioxide (CO2 ), and air by selectively venting the desired gas from compressed gas bottles into an evacuated vacuum chamber. The sensors provide a direct electrical readout in response to changes in high concentrations, from these bottles, of CO2, O2, nitrogen and argon, as well as changes in humidity from venting atmospheric air. From the signal response to each gas species, the relative graphene sensitivity to each gas is extracted as a relationship between the percentage-change in graphene's resistance response to changes in vacuum chamber pressure. Although there is virtually no response from O2, N2 and Ar, there is a sizeable cross-sensitivity between CO2 and humidity occurring at high CO2 concentrations. However, under atmospheric concentrations of CO2, this cross-sensitivity effect is negligible – allowing for the use of graphene-based humidity sensing in atmospheric environments. Finally, charge density difference calculations, computed using density functional theory (DFT) are presented in order to illustrate the bonding of CO2 and water molecules on graphene and the alterations of the graphene electronic structure due to the interactions with the substrate and the molecules.